Content of Nitrate, Phosphate, and Chlorophyll-a in Terkul Water, Rupat Strait, Riau - Ningrum, Indah Puspita; Nedi, Syahril; Mulyadi, Aras (Journal of Coastal and Ocean Sciences, 2022)
The waters of Terkul are related to the strait of Rupat. Around the Terkul area, there is an oil and gas industry with transportation, storage, processing, and distribution of oil supplies to various regions in Sumatra through ship transportation. This activity causes the waters of the Rupat Strait to be prone to oil pollution. Oil pollution can reduce the quality of the waters and cause nutrient content in the waters to decrease. Nutrients greatly affect the concentration of chlorophyll-a in the waters. Chlorophyll-a is a pigment capable of photosynthesis and is present throughout phytoplankton organisms. The purpose of this study was to analyze the association of nitrate concentration and phosphate concentration to chlorophyll-a. the study was conducted in April 2021. Waters sample was collected from the waters of Terkul and sample analysis was conducted in the Marine Chemistry Laboratory. The results of the study show that the association between chlorophyll-a and phosphate corresponds to the regression result of obtaining a value (r) of 0.67. Linearly shows a strong relationship